QR Code Reader pada Smartphone Android untuk Aplikasi Layanan Restoran - Adrianto, Dennise; Yesmaya, Violitta; Agung, Albertus; Ivander, Davin Timothy; Elysia, Elysia; Natalie, Nico (ComTech: Computer, Mathematics and Engineering Applications, 2015)
The development of today's smartphone technology has a huge impact to the world of information technology and telecommunications. The emergence of a variety of applications for smartphones can improve the performance and effectiveness of an activity. Some restaurants have made use of smartphones in the business process, but only as a recording medium order or see a list of menus available in the restaurant. The purpose of this paper is to make the application as a whole that integrated the frontend and backend operations that help the process from ordering food, serving customer to managing restaurant data such as restaurant menus, employees, and transactions. The method used is the method of analysis (study of literature, analysis of similar applications, questionnaires, and interviews) and extreme programming design method. The results of this research is frontend application for food ordering and restaurant service and a backend system that has additional features such as restaurant profiles, restaurant menu data includes descriptions, recommended menuand images, promos, restaurant rating or menu rating, the waiter call feature, view bill and request features bill. The conclusion of this research is the developed application can help ordering process and restaurant servicesprocess in a restaurant with good customer satisfaction and good application performance.